Sustainable Education at Higher Education Institutions (HEIs) and the COVID-19 Pandemic: A Bibliometric Review Study Field Review - Wadim Strielkowski; Elena N. Korneeva; Alexander K. Neshcheret; Lyudmila A. Sundeeva (National Research Mordova State University, 2024)
Introduction. Recent environmental concerns over global warming and climate change together with the calls for sustainable development highlighted the importance of sustainable education aimed at preparing the new generations to come for the universal challenges facing humanity. All of that has been reinforced by the recent COVID-19 pandemic that brought about the digital surge in education. The interest in the topic of sustainable education can be demonstrated by the surge of research publications on this topic indexed in the Web of Science database from merely 22 in 1991 to 4055 in 2022. The main goal of this study is to provide a comprehensive review of scholarly sources related to sustainable education in higher education institutions and the COVID-19 pandemic. Materials and Methods. The authors analyzed the vast body of recent research literature on sustainable education and conducted a field review. In total, 1115 results for the keywords "sustainable education" and "COVID-19" have been retrieved from the WoS database and subjected to the network analysis using VOSViewer software for identifying dominant trends, interconnectedness, and network visualization in the intersectoral research. Results. It was found that there has been s a significant increase in interest for sustainable education during the pandemic in the research literature, highlighting the shift in educational focus. Five main thematic clusters of research have been identified, such as university student teaching, health policy services, economic impacts, Sustainable Development Goals, or higher education, with a strong emphasis on the student experience and institutional responses. Additionally, the interdisciplinary nature of research in this area has been proved, covering health, technology, economics, and social policies. It has been confirmed that these recent changes in sustainable education in higher education emphasize the need for multifaceted approaches to address the challenges posed by the pandemic on education sustainability. Discussion and Conclusion. The challenges posed by the COVID-10 pandemic have made it increasingly clear that the higher education sector must go digital to succeed in a post-COVID world. Universities around the world must be prepared for future changes in industry, or they risk being left behind in an ever-changing landscape. The findings stemming from this study can be useful to ministries of education, various authorities and stakeholders, as well as to universities and higher education institutions themselves, both public and private, in the need to implement new approaches at all levels new bottom-up and on-the-ground approaches.